2020
DOI: 10.2169/internalmedicine.3248-19
|View full text |Cite
|
Sign up to set email alerts
|

Generation Gap for Screening and Treatment of Hepatitis C Virus in Saga Prefecture, Japan: An Administrative Database Study of 35,625 Subjects

Abstract: Objective Despite recent advances in hepatitis C virus (HCV) treatment, some HCV-positive individuals are unaware of their infection. The present study aimed to assess the rate and age distribution in Saga Prefecture regarding i) HCV infection and HCV screening and ii) direct acting anti-viral (DAA) treatment. Methods HCV screening data collected at a medical institution or in the workplace were obtained from the administrative database in Saga Prefecture between April 1, 2008 and March 31, 2014. DAA treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…17 In addition, we have shown the prevalence of HBs-Agpositive patients according to age in Japan in S1 Table, and the prevalences of presumptive HCV carriers according to age in both Saga prefecture and Japan in S1 and S2 Tables. 17,18 HBs-Ag positivity was defined as ≥0.05 IU/mL. HCV-Ab positivity was defined as ≥1.0 S/CO, but titers were further divided into three categories-low (≥1.0, <4.0 S/ CO), medium (≥4.0, <12.0 S/CO), and high (≥12.0 S/ CO) 19 -and only patients in the medium and high groups were considered positive for the purposes of subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…17 In addition, we have shown the prevalence of HBs-Agpositive patients according to age in Japan in S1 Table, and the prevalences of presumptive HCV carriers according to age in both Saga prefecture and Japan in S1 and S2 Tables. 17,18 HBs-Ag positivity was defined as ≥0.05 IU/mL. HCV-Ab positivity was defined as ≥1.0 S/CO, but titers were further divided into three categories-low (≥1.0, <4.0 S/ CO), medium (≥4.0, <12.0 S/CO), and high (≥12.0 S/ CO) 19 -and only patients in the medium and high groups were considered positive for the purposes of subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…(39)(40)(41) The incidence of bleeding induced by gastroesophageal varices has decreased during the most recent decade in Japan because the prevalence of portal hypertension due to liver cirrhosis and/or hepatocellular carcinoma has decreased with the reduction in the prevalence of viral hepatitis and progress in therapeutic approaches to viral hepatitis. (42)(43)(44)(45) Upper GI bleeding is a complication of GERD. The prevalence of GERD increased during the study period as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%